Theoretical contributions to the study of the Costa Rican educational system from critical thought - Barrientos Valverde, Jorge (2015)
The aim of this article is to provide a series of theoretical principles and conceptual explanations from critical thought, that with their respective authors provide some guidance for addressing topics referred to the analysis of contemporary educational systems taking into account the practical logic for which they have been made in the world of contemporary neoliberal capitalism system that governs us. So that aims to develop aproposal that serves those interested in the study and critical understanding of education or history of educational systems in Costa Rica and in general in Latin America, where they have similar perspectives.